PENGEMBANGAN PROTOTYPE WEB PARIWISATA PekanbaruView DAN PERSEPSI PEMAKAI TERHADAP DESAIN DAN KEMUDAHAN PENGGUNAANNYA (Studi Kasus Mahasiswa Fakultas Pertanian Universitas Riau) - Simarmata, Conni; Restuhadi, Fajar; ', Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Internet is one of the main of development of information technology. Trough the internet can also be obtained various information, among others tourism information. Tourism information are generally published in website. Pekanbaru city also has tourism. From websites that already exist in the pekanbaru city, show only general information of pekanbaru city. Seeing these conditions, researcher on prototype development of tourism web pekanbaruview, to meet the needs of tourists and society about tourism information pekanbaru. The purpose of this research : 1) Designing web application PekanbaruView tourism using Joomla 3.2  2)  To analyse expectations and attributes performance dimension of the tourism PekanbaruView web. Sampling using a convenience sampling and taking 75 samples. Analisys of the data using Joomla 3.2, and Importance and Performance Analysis (IPA). The result showed that to design a view of tourism web Pekanbaruview application, Previously the view of the tourism pekanbaruview web has designed. Furthermore, installing XAMPP as a server that supports the Joomla 3.2. and after that installing joomla 3.2. Based on the result of the IPA there is one attribute that is located on the first quadrant. The attributes is the speed of access. In the second quadrant there is seven atribut, Which is attributes top menu, picture flash, content, Clarity of the information, features on the website, newest  information, and ease of users. For attributes that in third quadrant is a view of interface of calendar. In the fourth quadrant there is three attributes, which is the accurate of the information, header, user satisfaction. Keywords : Tourism Web, User Perception, Joomla, Web Design